Coefficient of Performance (COP) evaluation of electric water-cooled chiller during partial/full load operation at PUTRAJAYA plant 1 - Mazlan, Luqman Hakim (IRC, 2020)
Air-conditioning and refrigeration system are the most energy consuming as the energy are needed to cool the system. COP stands for Coefficient of Performance and it is indicating the efficiency of heating and cooling machines. This study presents an evaluation of the COP of the water-cooled chiller, partial load and cool thermal storage. The objective of this paper is to evaluate the COP of water-cooled chiller at Putrajaya Plant 1. There are two types of chillers that are existed, it is air-cooled chiller and water-cooled chiller. The thermal storage can be used to reduce the amount of usage of the energy during peak hour as the demand for the cooling at the highest. The data (parameters that are related to chiller) are taken from the Putrajaya Plant 1 by minutes. Using COP model that was made by using Microsoft Excel, the data was taken out at every 1 hour and arranged by week starting from week 1, 2019 to week 8, 2019. The analysis can be made by tabulating the data and plotting. From the plotting, we can see the behavior of the COP throughout the week. This study provides the analysis and reasoning for the COP behavior to reduce the loses of energy in the chiller system.